Applications of solar radiation toward the slip flow of a non‐Newtonian viscoelastic hybrid nanofluid over a rotating disk. Issue 12 (18th September 2022) - Ramzan, Muhammad; Saeed, Anwar; Dawar, Abdullah; Lone, Showkat Ahmad; Kumam, Poom; Watthayu, Wiboonsak
Abstract: This work explores a semi‐analytical solution of the Magnetohydrodynamics (MHD) viscoelastic water‐based hybrid nanoliquid flow containing TiO2 and CoFe2 O4 nanoparticles past a rotating disk along with velocity slip condition. The impact of solar radiation is incorporated in the temperature equation. The current study consists of non‐Newtonian viscoelastic hybrid nanofluid flow problem which is comprised of momentum and temperature equations. By using suitable similarity transformations, the higher‐order nonlinear ordinary differential equations are transformed into the nonlinear ordinary differential equations and then resolved with the execution of the homotopy analysis scheme in MATHEMATICA 10.0. The behavior of the involved physical parameters on the hybrid nanoliquid radial and tangential velocities and temperature profiles are calculated in a graphical form. Also, the skin friction and Nusselt number for Ti O 2 − CoF e 2 O 4 / TiO_2-CoFe_2O_4/ /water nanoliquid are described in tabular form. Some major results related to the current work are that by rising the values of the viscoelastic parameter, nanoparticle volume fraction of the titanium dioxide and cobalt oxide increases the skin friction coefficient C g r C_gr . The viscoelastic parameter, nanoparticles volume fraction of the cobalt oxide and magnetic parameter reduced the skin friction coefficient C f r C_fr of the hybrid nanofluid. It is noted that Nusselt number is lower for both Q S R = 0 Q_SR = 0 and Q S R > 0 Q_SR > 0 cases against the absorption factor. The expansion in hybrid nanofluid temperature is examined for both Q S R = 0 Q_SR = 0 and Q S R > 0 Q_SR > 0 cases. It is obtained that the temperature and heat rate transfer of the hybrid nanofluid are dominant in the presence of solar radiation. Abstract : This work explores a semi‐analytical solution of the Magnetohydrodynamics (MHD) viscoelastic water‐based hybrid nanoliquid flow containing TiO2 and CoFe2 O4 nanoparticles past a rotating disk along with velocity slip condition. The impact of solar radiation is incorporated in the temperature equation. The current study consists of non‐Newtonian viscoelastic hybrid nanofluid flow problem which is comprised of momentum and temperature equations.…